Light emission properties of mechanical exfoliation induced extended defects in hexagonal boron nitride flakes. (1st July 2022) - Ciampalini, G; Blaga, C V; Tappy, N; Pezzini, S; Watanabe, K; Taniguchi, T; Bianco, F; Roddaro, S; Fontcuberta I Morral, A; Fabbri, F
Abstract: Recently, hexagonal boron nitride (hBN) has become an interesting platform for quantum optics due to its peculiar defect-related luminescence properties. Concomitantly, hBN was established as the ideal insulating support for realizing 2D materials devices, where, on the contrary, defects can affect the device performance. In this work, we study the light emission properties of hBN flakes obtained by mechanical exfoliation with particular focus on extended defects generated in the process. In particular, we tackle different issues related to the light emission in hBN flakes of different thicknesses in the range of hundreds of nanometers, revealing a higher concentration of deep level emission in thinner area of the flake. We recognize the effect of crystal deformation in some areas of the flake with an important blue-shift (130 meV) of the room temperature near band edge emission of hBN and the concurrent presence of a novel emission at 2.36 eV, related to the formation of array of dislocations. We studied the light emission properties by means of cathodoluminescence (CL) and sub-bandgap excitation photoluminescence of thickness steps with different crystallographic orientations, revealing the presence of different concentration of radiative centers. CL mapping allows to detect buried thickness steps, invisible to the scanning electron microscopy and atomic force microscopy morphological analysis.